Management in Perspective - Julius, Michael John; Schlender, William E. (Academy of Management Journal, 1962)
Discusses the results of a survey on the views of executives concerning future trends of personnel management and industrial relations. General trends and forces; Role of executives in decision-making; General knowledge and skills needed to meet future management challenges.